Empirical analysis of the illiquidity premia of German real estate securities - Thomas Paul; Thomas Walther; André Küster-Simic (Financial Markets and Portfolio Management, 2021)
In this study, we analyze illiquidity premia and their effect on the expected returns of German real estate securities. To this end, we use a unique data set that includes real estate stocks, real estate investment trusts (REITs), and open- and closed-end real estate funds for 2003–2017. We follow Amihud's (JFM 5:31–56, 2002) structural approach; specifically, we estimate Amihud's illiquidity factors, investigate the relationships between expected returns and illiquidity, and analyze the effects of expected and unexpected market illiquidity on future returns. We show that illiquidity plays an important role in expected returns for real estate stocks and investment trusts (REITs); however, it has less clear effects on open- and closed-end funds. We find that the adjusted ILLIQ includes appropriate correction factors for securities with low trading activity and is a useful improvement. We also find evidence of structural breaks in the relationship between returns and illiquidity.
Keywords: G11; G12; G14; 330; Asset pricing; Real estate; REITs; Risk-factors; Illiquidity